The role of morphological constituents in reading Finnish compound words. - Pollatsek, Alexander; Hyönä, Jukka; Bertram, Raymond (Journal of Experimental Psychology. Human Perception & Performance, 2000)
The processing of transparent Finnish compound words was investigated in 2 experiments in which eye movements were recorded while sentences were read silently. The frequency of the second constituent had a large influence (95 ms) on gaze duration on the target words, but its influence was relatively late in processing: A clear effect only occurred on the probability of a third fixation. The frequency of the whole compound word had a similar influence on gaze duration (82 ms) and influenced eye movements at least as rapidly as did the frequency of the second constituent. These results, together with an earlier finding that the frequency of the first constituent affected the first fixation duration, indicate that the identification of these compound words involves parallel processing of both morphological constituents and whole-word representations. Reprinted by permission of the publisher.